The most common deficiencies that obstruct the writing skills of composition I students of the Foreing Language Department of The School of Arts and Ciences fo The University of El Salvador in second semester of the year 2012 - Alvarado Reina, Ronald Enrique; Contreras Menjivar, Rodolfo Mauricio; Orellana Pineda, Noelia Beatriz (2024)
This investigation was aimed to find out the most common deficiencies of Composition I students’ English writing and consequently identify the weak points in the students ́ writings and then establish a prioritization of such in order to have a better knowledge on the right and precise course of action to be taken for further researchers. This study was carried out in the Foreign Language Department of the University of El Salvador. The subjects of this study were a total of 21 students randomly chosen from four different groups of Composition I. The data required for this study was gathered through four different instruments: two questionnaires to collect the points of view from teachers and students respectively. As well as a rubric to analyze students’ compositions and a check list to keep records of the class observation. The results of the study suggested that there are three kinds of errors that outstand as the most common errors in the students’ writings: Those related to Grammatical Deficiencies, those related to Coherence Deficiencies and finally those related to Mother Tongue Interference Deficiencies. In conclusion, the thesis argues that writing in English is essential in students’ process of learning a new language but that students should not be expected to be able to write good abstracts without assistance. This investigation hopes to offer all participants useful insights on writing in English, and thus, make a contribution to improving the general standard of students’ compositions.